OPTIMALISASI ALOKATIF INPUT USAHATANI JAGUNG MANIS HIBRIDA DI DESA BOCEK KECAMATAN KARANGPLOSO KABUPATEN MALANG - Avida Ilayna; Masyhuri Mahfudz; Sri Hindarti (Program Studi Agribisnis, 2020)
This study aims to determine the magnitude of farm income sweet corn hybrids in the village Bocek District of Karangploso Malang, determine the factors of production on the farm production of sweet corn hybrids in the village Bocek District of Karangploso Malang, analyze optimizing the use of factors of production of sweet corn hybrids in the Village Bocek Karangploso District of Malang. This research determined by purposive sampling in the village Bocek Karangploso District of Malang using simple random method using 40 samples of hybrid sweet corn growers. The analytical method used is cobb-Douglass function analysis and analysis of allocative efficiency of production inputs (NPMX / PX). The results showed the value of R / C ratio of 2.36, which means profitable and viable. Production factors which significantly affect the farming of sweet corn hybrid that is the seed and manure. Farmers in the allocation of production inputs is not efficient, because the value NPMX / PX of both factors of production is greater than 1. So in alokaatif, use of production factors have not been efficient hybrid sweet corn that need to be added use.